Relationship Between Mothers' Attitudes and The Practice of Exclusive Breastfeeding in Maros Regency - Nurlinda, Andi; Khairiyah, Winni Lailatul (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2025)
Background: Mothers’ knowledge and attitudes are important factors influencing the success of exclusive breastfeeding. This study aims to analyze the relationship between mothers' attitudes and the practice of exclusive breastfeeding for children aged 6-24 months in the working area of Mandai Health Center, Maros Regency.Method: The method used is quantitative with a cross-sectional approach. The study population comprises all mothers with children aged 6-24 months, totaling 87 individuals. The sample was determined using the total population sampling technique, thus the sample size is 87. The data analysis included both univariate and bivariate analyses.Result: The results showed that 75.9% of the mothers had a good attitude, 17.2% had a moderate attitude, and 6.9% had a poor attitude. Statistical tests revealed a significant relationship between mothers' attitudes and the practice of exclusive breastfeeding for children aged 6-24 months in the Mandai Health Center area (p = 0.000). The study concludes that there is a significant relationship between mothers' attitudes and the practice of exclusive breastfeeding in the Mandai Health Center working area. It is recommended that mothers maintain a positive attitude by requiring prospective and new mothers to read materials on the benefits of exclusive breastfeeding.